Biological and chemical studies of purified glycerol extracted from recycled used vegetable oils - Shehab Eldin Sayed Mohammed; Aliaa Mahmoud Issa; Saher Abdelhafeez Mazen; Wessam Taha Basal (Cairo : Shehab Eldin Sayed Mohammed, 2020)
Biodiesel has gained an increased popularity as a good alternative for fossil fuel because of its unusual qualities as a biodegradable, nontoxic and renewable diesel fuel. Hence, the economic utilization of the accumulated bioglycerol byproduct became critically important for the sustainability of biodiesel industry. The purified bioglycerol might be used as a valuable industrial stock in cosmetic, medical and food industries. However, if the purified product is going to be used in food, drug or any industry that involves its ingestion or skin contact by human or animals, the product should be thoroughly tested on animal models.The present study investigated the acute toxicity, anti-inflammatory, histopathological and genotoxic effects of zeolite-purified biogylcerol on different animal models. All the previous tests proved the ability of the purification process to improve the qualities of the crude bioglycerol to a degree comparable to the pharmaceutical grade glycerol. In other words, it could be concluded that zeolite-purified bioglycerol can be used in different industries that involves products consumed by human or animals
Thesis (M.Sc.) - Cairo University - Faculty of Science - Department of Zoology
Issued also as CD
Keywords: Acute toxicity; Anti-inflammatory; Bioglycerol